2013
DOI: 10.1186/1472-6963-13-458
|View full text |Cite
|
Sign up to set email alerts
|

Effects of immigrant status on Emergency Room (ER) utilisation by children under age one: a population-based study in the province of Reggio Emilia (Italy)

Abstract: BackgroundThe primary aim of this study was to assess the effect of immigrant status on Emergency Room (ER) utilisation by children under age one, considering all, non-urgent, very urgent, and followed by hospitalisation visits. The second aim was to investigate the role played by mother’s educational level in the relationship between citizenship and ER utilisation.MethodsThe cohort study included all healthy singleton live births in the years 2008–2009 and residing in the province of Reggio Emilia, followed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
31
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 31 publications
6
31
0
1
Order By: Relevance
“…This is consistent with reports that show Quebec to be the Canadian province with the highest percentage (24.9%) of residents without a family doctor [18]. Similar to previous research [17], we found that, compared to Canadian born mothers, immigrant mothers had increased odds of reporting difficulty accessing health care for their infant. Possible reasons behind immigrant mothers’ increased rates of reporting difficulty may be fewer relationships in the community, a poor knowledge of the Canadian health care system, and a lack of culturally appropriate care in the community [19], suggesting that a comprehensive strategy, which addresses multiple sources of immigrant mothers’ difficulty, may have the greatest effect on increasing health care access for immigrant women and their children.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with reports that show Quebec to be the Canadian province with the highest percentage (24.9%) of residents without a family doctor [18]. Similar to previous research [17], we found that, compared to Canadian born mothers, immigrant mothers had increased odds of reporting difficulty accessing health care for their infant. Possible reasons behind immigrant mothers’ increased rates of reporting difficulty may be fewer relationships in the community, a poor knowledge of the Canadian health care system, and a lack of culturally appropriate care in the community [19], suggesting that a comprehensive strategy, which addresses multiple sources of immigrant mothers’ difficulty, may have the greatest effect on increasing health care access for immigrant women and their children.…”
Section: Discussionsupporting
confidence: 92%
“…Terms used to describe NUP include low‐acuity, low‐urgency, inappropriate, non‐acute and primary care cases. Eleven studies defined NUPs using ED resources used during visit, while nine studies defined and categorised NUP using triage evaluation . In five studies, NUPs were defined as illnesses that could be seen in the primary care or outpatient setting within 24 h .…”
Section: Resultsmentioning
confidence: 99%
“…The predictors of NUP were assessed in 16 of the included studies. The predictors were associated with increased or decreased use of the ED for non‐urgent visits, see Table S2 (Supporting Information) . Using Anderson’ Healthcare Utilization Model, the predictors identified were predisposing, enabling and needs factors .…”
Section: Resultsmentioning
confidence: 99%
“…About 23 086 ED visits occurred between 2010 and 2013, and 32.4% of these visits were low acuity, resulting in costs to the health‐care system in excess of A$895 000–A$1 110 000 per year over the 4‐year study period. ED use for low‐acuity visits among paediatric patients is an international concern, with the proportions reported in various studies ranging from 15 to 90% . The costs estimated in this study are the costs that could have been saved if the children had presented at a GP clinic or other primary care centres.…”
Section: Discussionmentioning
confidence: 98%
“…The proportion of paediatric‐related low‐acuity ED visits ranges from 15 to 90% . Given that paediatric patients are a vulnerable population and require special care for growth and development, the continuous use of the ED for low‐acuity presentation places the child at an increased risk of poor continuity of care .…”
mentioning
confidence: 99%